Mask design for the reproducible fabrication and reliable pattern transfer for polysilicon nanowire - Tijjani Adam, Shuwa; Uda, Hashim, Prof. Dr.; Leow, Pei Ling (Institute of Electrical and Electronics Engineers (IEEE), 2013)
Link to publisher's homepage at http://ieeexplore.ieee.org/